2021
DOI: 10.1186/s12891-021-04764-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporary spanning plate across the elbow for complex fractures of the distal humerus

Abstract: Background Open reduction internal fixation (ORIF) is the gold standard management of fractures of the distal humerus. Stable fixation to allow early mobilization is not always possible in cases with comminuted fracture patterns and bone loss, with a high failure rate. We propose augmentation of internal fixation in these unstable situations with a spanning plate across the elbow to protect the fixation construct temporarily until bone union. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…With poor stability and difficulty in resisting the shear stress generated by the joint., [ 3 ] the cannulated screw would probably result in internal fixation failure and delayed healing, and even nonunion with necrosis of the distal humeral articular surface and elbow joint disability, and osteoarthrosis of the elbow. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With poor stability and difficulty in resisting the shear stress generated by the joint., [ 3 ] the cannulated screw would probably result in internal fixation failure and delayed healing, and even nonunion with necrosis of the distal humeral articular surface and elbow joint disability, and osteoarthrosis of the elbow. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…With poor stability and difficulty in resisting the shear stress generated by the joint., [3] the cannulated screw would probably result in internal fixation failure and delayed healing, and even nonunion with necrosis of the distal humeral articular surface and elbow joint disability, and osteoarthrosis of the elbow. [12] However, functional exercises within 3 weeks after surgical treatment is the key factor for functional recovery of the elbow joint. [8,13] Studies have shown that the probability of elbow stiffness after trauma is at least 5%, and if the range of motion of the elbow is less than 30° to 120°, it will seriously affect orthobiosis.…”
Section: Discussionmentioning
confidence: 99%
“…ORIF treatment for DHFs with an extensor mechanism-on approach can achieve favorable healing, a mean elbow flexion-extension exceeding 100°, and maintenance of 90% of elbow extension strength, relative to that of the contralateral, normal elbow [ 4 ]. Spanning the elbow temporarily with a plate as an adjunct to the ORIF method has been demonstrated to be simple and effective in achieving fracture stability and union and can minimize failure rates after fixation of DHFs [ 16 ]. However, a recent systematic review and meta-analysis revealed that complications and reoperations of DHFs after ORIF may be more frequent than previously understood [ 17 ].…”
Section: Introductionmentioning
confidence: 99%